2019
DOI: 10.3390/molecules24224119
|View full text |Cite
|
Sign up to set email alerts
|

A Nucleoside/Nucleobase-Rich Extract from Cordyceps Sinensis Inhibits the Epithelial–Mesenchymal Transition and Protects against Renal Fibrosis in Diabetic Nephropathy

Abstract: Cordyceps Sinensis, a traditional Chinese medicine and a healthy food, has been used for the treatment of kidney disease for a long time. The aim of present study was to isolate a nucleoside/nucleobase-rich extract from Cordyceps Sinensis (CS-N), determine the contents of nucleosides and nucleobases, and explore its anti-diabetic nephropathy activity. CS-N was isolated and purified by using microporous resin and glucan columns and the unknown compounds were identified by using HPLC-DAD and LC-MS. The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…There is accumulating evidence indicating that the RAF/MEK/ERK signaling pathway plays an important role in EMT during DKD. 35 , 36 It has been demonstrated that the response of ERK/MAPK signaling cascades activation to growth factors or mutant RAS could up-regulate TGF-β-induced EMT. 37 A previous study revealed that the RAF signaling pathway increases the expression of SNAIL1 and/or SNAIL2, thereby promoting cancer-associated EMT manifested as cell motility and invasive behavior upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence indicating that the RAF/MEK/ERK signaling pathway plays an important role in EMT during DKD. 35 , 36 It has been demonstrated that the response of ERK/MAPK signaling cascades activation to growth factors or mutant RAS could up-regulate TGF-β-induced EMT. 37 A previous study revealed that the RAF signaling pathway increases the expression of SNAIL1 and/or SNAIL2, thereby promoting cancer-associated EMT manifested as cell motility and invasive behavior upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Some relevant studies highlight new perspectives of TCM for delaying DN progression and strengthen the therapeutic rationale for TCM on the treatment of DN [ 23 , 24 ]. Cordyceps contains several active ingredients which affect multiple targets and pathways in the progression of DN and has been used as an adjuvant on the treatment of DN in China for a long time [ 7 , 25 ]. In this study, we selected 7 active ingredients from Cordyceps based on the OB and DL, including linoleyl acetate, arachidonic acid, cholesteryl palmitate, CLR, beta-sitosterol, cerevisterol, and peroxyergosterol.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies, renal brosis can be improved by blocking MAPK signaling pathway [41]. In vitro studies shown that, under high glucose, p38MAPK activation promotes renal tubular epithelial cell EMT progress [42], and p38 inhibitor SB203580 signi cantly reverses the EMT progress by downregulated the expression of E-Cadherin and type 1 collagen in HK-2 cells [43,44]. mTOR is a serine/threonine kinase, which belongs to the family of phosphatidylinositol kinase-related kinases.…”
Section: Discussionmentioning
confidence: 99%